İstanbul İçin Nüfus Ve İşgücü Yer Seçimi Etkileşimi - Kanıçok, Ferda (Fen Bilimleri Enstitüsü, 1995)
Nüfus ve işgücünün metropoliten alanda me kana al dağılımı sonucunda alt merkezler oluşmakla ve

The spatial relationships are getting more and more complex as the metropolitan areas keep on enlarging and consequently the environmental pollution and energy that are the results of the growing demand for transportation become the main problems that the planners are to solve. The development of the non- monoeentered metropolitan spatial structure, which is a spatial model having as its purpose the lessening of the distance between the residing and the laboring places, has been supported as it is believed to be capable to enhance the environmental quality.The spatial distribution of the employment power in the non-monocentered metropolitan areas affects and directs a wide spectrum of issues including the transportation, the industry, the business centers, the planning of residential areas and its affects on the environment. In addition to this, the factors affecting the selection of the functions’ position are required to be listed in the studies conducted on this same subject in order for the spatial structure to be more affective and the sources to be rational.The sub-centers are formed as a result of the spatial distribution of the population and the productive power and so the city is transformed into a non-monocentered urban settlemnts. The determination of the direction of this transformation affects the growth and the development of the city (by affecting the value of the land and the residences).In Istanbul, which is the greatest matropol of Turkey of mono-centered spatial structure is transformed into a non-monocentered one as the historical canter located on the peninsula iceep on losing its relative importance. The servicing industry is dominant in the sub-centers that have coma into being as a result of this development. The supporting of the production industry in particular is also vital in this transformation period. There is an overpopulation in the urban area in general, that has become a mojer problem especially after the 1950' s, as aresult the growing migration and birth rates. The reason for the decrase in the population in areas near the sub-centers while thera is an icraase in general in the city is the fuctional transformation of the residences into offices. The article includes five chapters and the first one contains the reason why this subject is selected as well as the purpose and the scope of this study.in the second chapter, the economical and behavioral approaches are considered to be the principal factors in explaining the spatial distribution of the population and the employment. These approaches are based on the position selection and equilibrium theories and have as their fundemantel principles the maximising of the income and the minimising of the cost. There are two main models for this kind of approach: the monocentered urban development model and the non- monocentered urban development model. In the section related to the mono-centered urban development model, the ideas of Alonso, Muth-Mills, V.Thilnen and A.Weber on the topic of the location selections for the firms and the residences are discribed. Alonso and Muth-Mills focused on the location selection for the residences and claimed that the use and the value of the land, the ability to be reached easily and the rent rates are the major factors affecting this selection while A.Weber and V.Thünen focused on the location selection for the fima and claimed that the studies for tha maximising of tha income and tha minimising of tha cost(especialy tha transportación cost), tha value of tha land and relativa mar feat prices ara tha major factors affecting this selection. Tha studies concerning tha non-iaonocantarad development models related to tha location selections in tha spatial distribution of tha population and the employment are continuing.In tha third chapter, the urbanization process and the changes in tha population and tha employment are evaluated in Istanbul which is tha greatest metropolitan of Turkey, tha changes in tha population and tha productive power of tha Marmara region that ara related to tha attraction of Istanbul and tha relationship between Istanbul and tha whole of Turkey are examined. Tha increase in tha population of tha urban areas started in tha 1950's. Tha raasan for this inraasa is the migration from tha rural areas to tha urban areas. Istanbul plays a major role in tha increase of tha population of the urban areas and rata of migration to tha urban areas in Turkey in general. Tha rata of population increase in Istanbul is greater by 2.5 folds than tha rate of population increase in the whole of Turkey. However as the increase in tha rata of employment is not paralel to the increase areas in tha population, tha rata of dependence on tha laboring indivuduals increased. The reason for this increase is that tehere is no equilibrum in the Turkish economy.Istanbul, that had developed radiantingly around centers like Eminönü* Üsküdar and Kadıköy between 1930 and 1950 in spite of the low increasing rata in the population and tha employment, was affected by tha planning decisions. Tha foreign planning experts hava been consultad to at tha tima and tha city planner H.Frost contributed a great deal to the planning of the city. The urban settlements were developing around some centers as a result of the estabilishment of some factories in Paşabahçe, Beykoz, şişli, Sarıyer, Bakırköy and Zeytinburnu before the declaration of the republic, municipal, plans and the intensifying of the industry facilities around Haliç. The squatter settlement has started in a small scale in this period in Zeytinburnu and Osmaniye settlements. The migration rate increased between 1950 and 1965 as a result of the modernization process in agriculture. İstanbul, which was not ready to meet the demands of the increasing population regarding the technical and social infrastructure, the equipment and the service industries, has started to enlarge towards Beyoğlu, Beşiktaş and şişli on the European side and towards the east of Üsküdar and Kadıköy on the Asian side the road axis that have bean newly constructed and expanded by Menderes and Högg. while the industrial area around Haliç has grown to include the northern districts of Eyüp, Rami, Gaziosmanpaşa, Alibeyköy and Kağıthane, the other industrial growth around Zeytinburnu and Bakırköy spreaded in the direction of Halkalı, Sefaköy and Firuzköy. The Haliç-Bomonti- Büyükdere road became busier around Beyoğlu and the industrial area in the Asian side around Kartal-Maltepe which has been spreading linearly started to widen towards Tuzla-Yakacık-çayırova-Gebze axis.The population was decreasing in Eminönü while it was increasing around the same district. The population and employment increased rapidly and started to spread around the central laboring and industrial areas in Fatih, Bakırköy and Kartal. The need for housing could not be served in this period because of the alarming rate of increase. As a result of this and to minimise the transportation costs, squatter settlements constituted around Zeytinburnu, Taşlıtarla, Osmaniye, Küçükköy, Beşyüzevler, Bereç, şirinevler, Alibeyköy, Kağıthane, Sarıyer, Beykoz, Üsküdar, Ümraniye and Kadıköy. The controlling of the planning of the city became harder because of the rapid development of this well-organized squatter movement. The metropolitan area of İstanbul started to expand towards the east on the Asian side to towards the north-west on the European side as a result of the increase in the population and in the employment, the getting easier to reach the industrial areas and the spreading of the industrial and trading areas. There have been many studies for the planning of the city between 1965 and 1995. The major ones are the 1966 Industrial Areas City Plan, the 1980 Metropolitan Area city Plan and the 1994 Istanbul Metropolitan Area city Plan. There have been no remarkable results in the planning efforts made between 1966 and 1980. The planning problems of Istanbul have been tried to be solved with the action programs during this period of time. The industrial areas with in the urban settlement enlarged towards Beykoz, Ümraniye, Kartal, Pendik and Tuzla on the Asian side and towards şişli, Kağıthane, Sarıyer, Eyüp, G.o.Paşa, Güngören, Esenler, Bağcılar, K.Çekmece, Bahçelievler and Esenyurt areas on the Europen side between 1965-1995. The spreading of the industrial areas to the urban areas resulted in the increasing of the population and of the rate of migration to the urban areas. The construction efforts around the industrial areas that has begun earlier as a result of the need to be close to the working places, continued at this period. The population increase was at its peak point in Bakırköy and Kartal between 1965-1995, the reason for this being these areas developing as the areas providing new incomes. The population started to spread in the metropolitan area according the urban development of Istanbul directed itself -towards the coastal roads with the construction of Bosphorus Bridge and the surrounding highways in 1973. The same development accelerated when the Fatih Sultan Mehmet Bridge and the surrounding DC highways have bean opened. The central business disrict in Beyoğlu, şişli and Mecidiyeköy have enlarged until Maslak in the north as a result of the decentralization of the central properties of the central business district of historical peninsula, Eminönü. The central business district have developed towards Eminönü, Bakırköy and Bağcılar in the east. on the Asian side, the central business disrict of Üsküdar and Kadıköy, Kartal and Maltepe have become third rate central business district. with in the decentralization of the industry and the spreading of the urban development between 1965 and 1995, there was born a growing demand for housing and so started the problem of squatter settlements. The squatter settlements, that have been constructed solely to serve the need for housing at the begining, became buildings up to seven storeys high in time because of the commercial needs arisen during this period. The squatter settlements have developed towards K. Çekmece, G.O.Paşa, Bağcılar, Esenyurt, Alibeyköy, Kağıthane, Sarıyer, Beykoz, Üsküdar, Ümraniye, Sarıgazi, Sultanbeyli and Kartal in the metropolitan area of Istanbul. The policies that will affect the use of land and the spatial formation of the transportation in the long run are principally the decisions to control the migration over the whole of country. The metropolitan area of Istanbul developed as a result of the continuing trend of today* s distribution of population and employment, the settlements of the population and the employment in a more centralized way in a short period of time, the densening of the population along the main transportation corridors because of the growing demand for public transportation and the formation of the subcenters with the development of several centers as employment centers apart from the main centers.in the fourth chapter, the transportation, the value of land and the changes in population and productive power that affect the spatial distribution of the population and the employment of Istanbul are examined and their affects are studied with the multi- recretion method. This model is valid for 14 districts that can be listed as Bakırköy, Beşiktaş, Beykoz, Beyoğlu, Eminönü, Eyüp, Fatih, G.O.Paşa, Kadıköy, Kartal, Sarıyer, şişli, Üsküdar and Zeytinburnu that are with in the borders of the Istanbul Greater Municipality. The 1985 and 1990 datas of DİE (National Statistics Enstitute) concerning the population and the employment, mod land values and the distances between the disricts have been used. The final model shows that the population and the productive power affect each other in the Intanbul urban area.in the final chapter, a general evaluation that stresses the effect on the spatial development of Istanbul of the increase of the population and the employment in the metropolitan area of Istanbul and the formation of the sub-areas with the support of the environmental approaches because of the decrease in the air pollution and the conservation of energy as aresult of the decreasing distance between the home and the office, can be found.
Location Of Employement And Population İn İstanbul
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Nüfus; Population; İş gücü; İstanbul; Workforce; Istanbul